2007
DOI: 10.1364/oe.15.017613
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a cosh-Gaussian beam through an optical system in turbulent atmosphere

Abstract: The propagation of a cosh-Gaussian beam through an arbitrary ABCD optical system in turbulent atmosphere has been investigated. The analytical expressions for the average intensity at any receiver plane are obtained. As an elementary example, the average intensity and its radius at the image plane of a cosh-Gaussian beam through a thin lens are studied. To show the effects of a lens on the average intensity and the intensity radius of the laser beam in turbulent atmosphere, the properties of a collimated cosh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Based on the extended Huygens-Fresnel diffraction integral formula, the propagation eqation of laser beam through the ABCD optical system in atmosphere turbulence can be written as [2][3][4][5][6][7][8][9][10][11][12]:…”
Section: Propagation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the extended Huygens-Fresnel diffraction integral formula, the propagation eqation of laser beam through the ABCD optical system in atmosphere turbulence can be written as [2][3][4][5][6][7][8][9][10][11][12]:…”
Section: Propagation Theorymentioning
confidence: 99%
“…And the optical system used in experiment will influence the evolution properties of laser beams propagating in turbulent atmosphere. Since the propagation of a laser beam propagation through an optical system in turbulent atmosphere is studied [2], various laser beam propagation through an optical system in turbulent atmosphere have been investigated, such as cosh-Gaussian beam [3], random electromagnetic beam [4], partially coherent cosine-Gaussian [5], stochastic electromagnetic Gaussian Schellmodel beam [6], radially polarized partially coherent beam [7], four-petal Gaussian [8], cylindrical vector Laguerre-Gaussian beam [9], elliptical Gaussian beam [10], annular vortex beam [11], four-petal Gaussian vortex beam [12] et al and with the development of laser technology, a new beam called flat-topped vortex hollow beam has been introduced and studied widely [13][14][15]. However, owing to its interesting properties and potential applications, the vortex beam has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Propagation of HSG laser beams in free space, in complex optical systems, in turbulence and in Kerr media have been studied extensively [14][15][16][17][18][19][20]. These studies indicate that the shape of HSG laser beams changes during propagation.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that incoherent combinations of cosh-Gaussian beams can also produce flattened beam patterns [17]. Due to the above productive characteristics of cosh-Gaussian beams, many works relating to propagation properties of such beams in various media have been intensively carried out [13,15,[18][19][20]. Very recently, the higher-order coshGaussian (HOCG) beam, which is defined as a higherorder cosh function multiplied by a Gaussian function, has been introduced as the superposition of decentered Gaussian beams or cosh-Gaussian beams [21].…”
Section: Introductionmentioning
confidence: 99%